Short-term effectiveness of intravitreal Ziv-Aflibercept for the treatment of macular edema secondary to retinal vein occlusion - Munayco-Guillén , Fernando (2025)
Objective: To determine the short-term effectiveness of intravitreal Ziv-Aflibercept (IV-ZA) for the treatment of macular edema secondary to retinal vein occlusion (MESRVO). Methods: A retrospective, single-arm cohort study was conducted, including patients diagnosed with MESRVO. All received six monthly doses of IV-ZA. Data was collected before treatment and one month after the final dose. The main outcome measures were best-corrected visual acuity (BCVA, LogMAR) and central macular thickness (CMT). Summary statistics were presented, and the Wilcoxon signed-rank test with continuity correction was used; p < 0.05 was considered statistically significant. Data were analyzed using R Studio. Results: Twenty-six eyes from 25 patients were included (69% with central retinal vein occlusion and 31% with branch retinal vein occlusion). Sixty-eight percent were male, with a mean age of 63.9 ± 13.4 years. Baseline BCVA was 2 (0.3–2.09) LogMAR, improving to 1 (0.09–2) LogMAR (p < 0.01). Baseline CMT was 671 (392–1174) µm, decreasing to 207 (137–325) µm after treatment (p < 0.01). A total of 92.3% of eyes achieved a CMT below 300 µm after therapy. No ocular or systemic adverse events were reported. Conclusions: Six-monthly doses of IV-ZA were effective for the short-term management of MESRVO, showing significant visual and anatomical improvement. IV-ZA may represent a safe and cost-effective therapeutic alternative.